Control of Nausea and Vomiting in Patients Receiving Anthracycline/Cyclophosphamide Chemotherapy for Breast Cancer - Nawa-Nishigaki, Minako; Kobayashi, Ryo; Suzuki, Akio; Hirose, Chiemi; Matsuoka, Rie; Mori, Ryutaro; Futamura, Manabu; Sugiyama, Tadashi; Yoshida, Kazuhiro; Itoh, Yoshinori (Anticancer research, 2018)
Chemotherapy-induced nausea and vomiting (CINV) is one of most distressing adverse events during cancer chemotherapy. In breast cancer patients receiving anthracycline and cyclophosphamide (AC) chemotherapy, CINV is poorly controlled. The prevalence of guideline-consistent antiemetic medication and control of CINV were investigated retrospectively in breast cancer patients receiving the first cycle of AC chemotherapy. Risks for CINV were analyzed by the multivariate logistic regression analysis. The effect of olanzapine added to the standard antiemetic medication on the incidence of CINV was subsequently evaluated in separate patients who received the first cycle of AC chemotherapy. Although the guideline-consistent antiemetic medication was performed in all subjects, the control rate of nausea (32%), but not vomiting (78%) was low. Risk analysis indicated that age younger than 55-year-old was a significant factor that reduces the control of both nausea and vomiting. Olanzapine (5 mg/day for 5 days), when added to the standard three-drug antiemetic medication, significantly improved the control of nausea and complete response. CINV was poorly controlled in breast cancer patients receiving AC chemotherapy, in which age younger than 55-year-old was a significant risk for both nausea and vomiting. Olanzapine was effective for improvement of the control of CINV associated with AC chemotherapy. Therefore, care should be taken to prevent CINV in young patients receiving AC chemotherapy by adding olanzapine to the standard three-drug antiemetic medication.